2007
DOI: 10.1111/j.1439-0507.2007.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and pharmacokinetic study of oral terbinafine for hyperkeratotic type tinea pedis

Abstract: SummaryTo study and establish an optimal administration method of oral antifungal, terbinafine (TBF), for hyperkeratotic type tinea pedis, from the pharmacokinetic point of view, 20 patients with hyperkeratotic type tinea pedis were given TBF 125 mg once daily for 4 weeks and observed over time for improvement in dermatological symptoms and mycological efficacy. Targeting five of the patients, TBF concentration in the stratum corneum was measured using the liquid chromatography ⁄ tandem mass spectrometry (LC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Another study used a lower dose of terbinafine at 125 mg OD and found that the concentration in the stratum corneum in hyperkeratotic type tinea pedis cases, was 247.80 ng/g, which was approximately 50 times higher than the MIC (3–5 ng/ml) at 1-week posttreatment, and was still higher than the MIC, at 50.73 ng/g, 6-week posttreatment. [ 9 ] Hence, at conventional doses (125–250 mg), the drug is not only secreted preferentially through the sebum-to-lipid rich sites but also achieves higher levels than the serum. Thus, with conventional doses, MIC levels are thus, there is little rationale for a higher dose as seen in this study.…”
Section: Clinical Application and Skin Pharmacokinetic Levelsmentioning
confidence: 99%
“…Another study used a lower dose of terbinafine at 125 mg OD and found that the concentration in the stratum corneum in hyperkeratotic type tinea pedis cases, was 247.80 ng/g, which was approximately 50 times higher than the MIC (3–5 ng/ml) at 1-week posttreatment, and was still higher than the MIC, at 50.73 ng/g, 6-week posttreatment. [ 9 ] Hence, at conventional doses (125–250 mg), the drug is not only secreted preferentially through the sebum-to-lipid rich sites but also achieves higher levels than the serum. Thus, with conventional doses, MIC levels are thus, there is little rationale for a higher dose as seen in this study.…”
Section: Clinical Application and Skin Pharmacokinetic Levelsmentioning
confidence: 99%
“…21 In 2008, Kawana et al performed a study on the concentrations of terbinafine in the stratum corneum and the efficacy of treatment in hyperkeratotic-type tinea pedis. 22 This study treated 20 patients, who had failed other therapies, with oral terbinafine 125 mg daily for 4 weeks and observed for 8 weeks post-treatment. Throughout the study, five patients were used to study the terbinafine concentration in the stratum corneum.…”
Section: Side Effects and Adverse Drug Reactionsmentioning
confidence: 99%